FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA KARYAWAN PABRIK ROKOK PRAOE LAJAR DI SEMARANG - Nindya Kurnia Aprinta; Kusyogo Cahyo; Ratih Indraswari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Chronic Obstructive Pulmonary Diseases (COPD) is lung diseases characterized by airflow obstruction. COPD is one of the causes of death in high-to-low income countries. The distribution data of cases of COPD in Semarang City by 2015, there are 670 cases. One of the risk factors of COPD is the use of PPE especially can protect the respiration system. This research aimed to analyze the factors that relate to the behavior of PPE usage of tobacco factory’s employees.This was a quantitative research and cross-sectional study design. Using simple random sampling, the sample of this taken as many as 46 employees. Data collected by indepth interview using questionnaire and spirometry. This research use univariate and bivariate analysis.All respondents are women. Most respondents are in the age range 18-40 years (65,2%), only small amount of respondents non-school (4,3%), and most of respondents has a working period of less than 10 years (60,9%). Most of respondents have a good PPE usage behavior (65,2%). The chi-square test showed that working period (p=0,001), availability of work regulation (p=0,0001), coworking support (p=0,0001), and manager support (p=0,0001) are significantly related to usage PPE behavior on the tobacco factory’s employees. While the variables of age, education, occupation, knowledge of PPE usage, attitude of PPE usage, and availablity of PPE are not significantly related to PPE usage behavior of tobacco factory’s employees.It was suggested to the manager and the agency to provide direction on the use of PPE.